2021
DOI: 10.17159/2411-9717/1272/2021
|View full text |Cite
|
Sign up to set email alerts
|

Effects of flotation operational parameters on froth stability and froth recovery

Abstract: SYNOPSIS The effect of flotation operational parameters on froth stability and froth recovery was studied. Froth stability was measured using a special column. To determine the froth recovery, the froth height change model and froth height exponential model were used. It was found that since the interactions between the pulp and froth zones affect the time of froth formation, the exponential model is more suitable than the froth height change method for determining the froth recovery. The results showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…It was also reported that the amount of collector affects the froth stability. In recent work, the researchers [31] examined the separation of particles during bubble coalescence, and they found that increasing the collector dosage increases the rate of froth formation, reduces the bubble coalescence, and, thus, the froth stability.…”
Section: Bench Scale Flotation Testsmentioning
confidence: 99%
“…It was also reported that the amount of collector affects the froth stability. In recent work, the researchers [31] examined the separation of particles during bubble coalescence, and they found that increasing the collector dosage increases the rate of froth formation, reduces the bubble coalescence, and, thus, the froth stability.…”
Section: Bench Scale Flotation Testsmentioning
confidence: 99%
“…This analysis meets a particular condition. It illustrates estimation-related problems because the parameters must be adjusted to a specific reference, considering the flotation process variability or adding a third pressure measurement point located in the froth zone [31][32][33][34][35][36].…”
mentioning
confidence: 99%